Immunohistology of rheumatoid nodules and rheumatoid synovium. Issue 5 (May 1988) - Athanasou, N A; Quinn, J; Woods, C G; Mcgee, J O
Abstract : The immunohistological features of rheumatoid nodules and rheumatoid synovium were examined using monoclonal and polyclonal antibodies raised against macrophages, HLA-DR, leucocyte common antigen, and immunoglobulin components. The palisading cells surrounding the necrotic centre of the rheumatoid nodule were shown to be HLA-DR positive leucocytes, mostly histiocytes. The inflammatory infiltrate associated with rheumatoid nodules showed many immunohistochemical similarities to that of rheumatoid synovium, including a preponderance of IgG positive plasma cells, and a similar number and microanatomical pattern of distribution of HLA-DR positive cells. The significance of these findings for the cellular immunopathology and aetiology of the rheumatoid lesion is discussed.